(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Bronchial asthma is one of the most common chronic respiratory diseases in children, which can significantly worsen their quality of life and damage the respiratory system. In this article, the main causes of the development of bronchial asthma and the prevalence of the disease, as well as the role of the nurse practitioner in their prevention, are considered. Particular attention is paid to various aspects of treatment, including drug treatment, disease prevention, as well as the role of parents and educational institutions in overcoming the disease in children.